Photoepilation and skin photorejuvenation: an update - Alessandro Martella; Mauro Raichi (PAGEPress Publications, 2017)
The effectiveness of intense pulsed light (IPL) and laser devices is widely accepted in aesthetic dermatology for unwanted hair removal and treatment of a variety of cutaneous conditions. Overall, most comparative trials have demonstrated similar effectiveness for IPL and laser devices. Literature studies alternatively favor the IPL and laser concepts, but the incidence of severe local pain and side effects were generally lower with IPL. IPL phototherapy, already established as a sound option in photoepilation and treatment of photoaging, hyperpigmentation and other skin conditions, is also considered first choice in the phototherapy of skin vascular malformations. When treating large areas, as often required in photoepilation and many aesthetic dermatology indications, IPL technologies show advantages over laser-based devices because of their high skin coverage rate. Compared to lasers, the wide range of selectable treatment settings, though a strong advantage of IPL, may also imply some more risk of local thermal side effects, but almost only in the hands of poorly trained operators. Overall, the strongest advantages of the IPL technologies are robust technology, versatility, lower purchase price, and the negligible risk of serious adverse effects in the hands of skilled and experienced operators.